TRADISI KATOBA PEMBENTUK KARAKTER ANAK DI MUNA - Hesti Hesti; Ahmad (Department of Early Childhood Education, STKIP Bina Bangsa Getsempena, 2021)
The purpose of this research is to describe the process of the Katoba tradition as a character forming of children in the Muna ethnic community, and to find the meanings of the Katoba tradition as forming children's character in the Muna ethnic community. This research was conducted in Lawa Subdistrict, West Muna Regency. The determination of informants in this study was carried out by determining key informants who served as pioneers for researchers to obtain data. The type of data in this study is qualitative data. Data collection techniques used in this study were: Observation, In-depth Interviews, and Documents. The results showed that the process of the katoba tradition as forming children's character in the Muna ethnic community consisted of 3 stages, namely: 1. the pre-katoba stage, which started with determining the good day of our life, 2. The catoba procession stage which began with: a. opening, b. dofotoba, c. listen to katoba advice containing lansaringino expressions, expressions of naasi rights, and expressions of maintaining the balance of the relationship between nature and the environment. 3. Post katoba (recitation of the prayer congratulations). The meaning contained in the process of implementing Katoba is in the hope that children who are told can understand the boundaries of ethics, norms in social life and can apply them in everyday life. The stages of the process of implementing katoba as forming children's character have a meaning that is believed by the Muna ethnic community, where the meaning cannot be separated from the cultural and belief context. The meaning contained in the process of implementing katoba in the Muna ethnic community is in the hope that the child who is said to be able to understand the boundaries and ethics or norms in social life, and can apply it in everyday life. Abstrak Tujuan penelitian ini adalah untuk mendeskripsikan proses tradisi katoba sebagai pembentuk karakter anak pada masyarakat Etnis Muna, dan untuk menemukan makna-makna tradisi katoba sebagai pembentuk karakter anak pada masyarakat Etnis Muna. Penelitian ini telah dilaksanakan di Kecamatan Lawa Kabupaten Muna Barat. Penentuan informan dalam penelitian ini di lakukan dengan menetapkan informan kunci yang berfungsi sebagai pembuka jalan bagi peneliti untuk memperoleh data. Jenis data dalam penelitian ini adalah data kualitatif. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah: Pengamatan , Wawancara Mendalam, dan Dokumen. Hasil penelitian menunjukan bahwa proses tradisi katoba sebagai pembentuk karakter anak pada masyarakat Etnis Muna terdiri dari 3 tahapan yaitu: 1. tahap pra – katoba, yang dimulai dengan menentukan hari baik dan ali kita, 2. Tahap prosesi katoba yang dimulai dengan : a. pembukaan, b. dofotoba, c. mendengarkan petuah katoba yang berisi ungkapan lansaringino, ungkapan haku naasi, dan ungkapan menjaga keseimbangan hubungan alam dan lingkungan. 3. Pasca katoba (pembacaan doa selamat). Makna yang terdapat dalam proses pelaksanaan katoba adalah dengan harapan anak yang di toba dapat memahami batasan etika , norma-norma dalam kehidupan bermasyarakat serta dapat mengaplikasikan dalam kehidupan sehari-hari. Tahapan proses pelaksanaan katoba sebagai pembentuk karakter anakmemiliki makna yang dipercayai oleh masyarakat etnis Muna, dimana pemaknaan tersebut tidak lepas dari konteks budaya dan kepercayaan. Makna yang terdapat pada proses pelaksanaan katoba pada masyarakat etnis Muna adalah dengan harapan anak yang di katoba dapat memahami batasan dan etika atau norma-norma dalam kehidupan bermasyarakat,serta dapat mengaplikasikan dalam kehidupan sehari-hari. Kata Kunci: Tradisi, Katoba, Pembentuk Karakter Anak